Innovative Stackable Multijet-Printed Templates for Precise Veneer Preparation: A Dental Technique - Xin Guan; Chunxu Liu; Teoh Feng Sheng; Yew Hin Beh; In Meei Tew (Applied Sciences)
Achieving precise veneer preparation is essential for optimal esthetic outcome and bonding strength. Advancements in digital technology enable the design and fabrication of stereolithographic templates to guide veneer preparation, significantly improving precision compared to conventional free-hand and silicone guide techniques. Therefore, this study outlines a digital workflow for designing and fabricating a series of Multijet-printed templates following the four essential steps of veneer preparation. The proposed workflow integrates virtual tooth preparation, virtual template design, and fabrication using an additive manufacturing approach and veneer preparation guided by the stackable Multijet-printed template. The result showed that the tooth reduction depth closely matched the required tooth reduction volume in three-dimensional accuracy analysis when using this innovative approach. This marks a transformative development in CAD/CAM dentistry, offering a more predictable and precise approach for veneer preparation, ultimately leading to improved clinical outcomes.